AN ANALYSIS OF TRANSLANGUAGING PRACTICES IN AN INDONESIAN EFL CLASSROOM - Amir, Fitrah Al; Atmowardoyo, Haryanto; Sakkir, Geminastiti (Universitas Negeri Makassar, 2023)
This study aimed to find out about in what situation and reason of the teacher to do translanguaging. This research used a qualitative descriptive method and the data was collected through observation and interview. The observation process was carried out in two meetings in class IX.2 SMPN 4 Bulukumba and the interview process was conducted with a teacher. The finding showed that the teacher often practiced translanguaging during the learning process in her class. The teacher usually did translanguaging when greeting students, introducing the lesson, drawing students’ attention, explaining the material, asking questions, giving tasks/commands, summarizing the lesson, and closing the meeting. The reason teacher did translanguaging was so that students understand the material being taught better. Based on the findings of the study, it can be concluded that the implementation of translanguaging has a positive impact in the process of teaching and learning English in EFL classroom.